Predictors of Treatment Attrition Among an Outpatient Clinic Sample of Youths With Clinically Significant Anxiety - Gonzalez, Araceli (Springer US, 2010)
Predictors of treatment attrition were examined in a sample of 197 youths (ages 5–18) with clinically-significant symptoms of anxiety seeking psychotherapy services at a community-based outpatient mental health clinic (OMHC). Two related definitions of attrition were considered: (a) clinician-rated dropout (CR), and (b) CR dropout qualified by phase of treatment (pre, early, or late phases) (PT). Across both definitions, rates of attrition in the OMHC sample were higher than those for anxious youths treated in randomized controlled trials, and comorbid depression symptoms predicted dropout, with a higher rate of depressed youths dropping out later in treatment (after 6 sessions). Using the PT definition, minority status also predicted attrition, with more African-American youths lost pre-treatment. Other demographic (age, gender, single parent status) and clinical (externalizing symptoms, anxiety severity) characteristics were not significantly associated with attrition using either definition. Implications for services for anxious youths in public service settings are discussed. Results highlight the important role of comorbid depression in the treatment of anxious youth and the potential value of targeted retention efforts for ethnic minority families early in the treatment process.